The impact of COVID-19 lockdowns on surface urban heat island changes and air-quality improvements across 21 major cities in the Middle East. (1st November 2021) - El Kenawy, Ahmed M.; Lopez-Moreno, Juan I.; McCabe, Matthew F.; Domínguez-Castro, Fernando; Peña-Angulo, Dhais; Gaber, Islam M.; Alqasemi, Abduldaem S.; Al Kindi, Khalifa M.; Al-Awadhi, Talal; Hereher, Mohammed E.; Robaa, Sayed M.; Al Nasiri, Noura; et al.
Abstract: This study investigates changes in air quality conditions during the restricted COVID-19 lockdown period in 2020 across 21 metropolitan areas in the Middle East and how these relate to surface urban heat island (SUHI) characteristics. Based on satellite observations of atmospheric gases from Sentinel-5, results indicate significant reductions in the levels of atmospheric pollutants, particularly nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), and carbon monoxide (CO). Air quality improved significantly during the middle phases of the lockdown (April and May), especially in small metropolitan cities like Amman, Beirut, and Jeddah, while it was less significant in "mega" cities like Cairo, Tehran, and Istanbul. For example, the concentrations of NO2 in Amman, Beirut, and Jeddah decreased by −56.6%, −43.4%, and −32.3%, respectively, during April 2020, compared to April 2019. Rather, there was a small decrease in NO2 levels in megacities like Tehran (−0.9%) and Cairo (−3.1%). Notably, during the lockdown period, there was a decrease in the mean intensity of nighttime SUHI, while the mean intensity of daytime SUHI experienced either an increase or a slight decrease across these locations. Together with the Gulf metropolitans (e.g. Kuwait, Dubai, and Muscat), the megacities (e.g. Tehran, Ankara, and Istanbul) exhibited anomalous increases in the intensity of daytime SUHI, which may exceed 2 °C. Statistical relationships were established to explore the association between changes in the mean intensity and the hotspot area in each metropolitan location during the lockdown. The findings indicate that the mean intensity of SUHI and the spatial extension of hotspot areas within each metropolitan had a statistically significant negative relationship, with Pearson's r values generally exceeding - 0.55, especially for daytime SUHI. This negative dependency was evident for both daytime and nighttime SUHI during all months of the lockdown. Our findings demonstrate that the decrease in primary pollutant levels during the lockdown contributed to the decrease in the intensity of nighttime SUHIs in the Middle East, especially in April and May. Changes in the characteristics of SUHIs during the lockdown period should be interpreted in the context of long-term climate change, rather than just the consequence of restrictive measures. This is simply because short-term air quality improvements were insufficient to generate meaningful changes in the region's urban climate. Graphical abstract: Ranking the 21 metropolitans in the Middle East according to the score computed for each atmospheric pollutant. The right panel indicates the air quality aggregated index during the lockdown period in 2020, accounting for the full range of atmospheric pollutants. Image 1 Highlights: COVID-19 impacts on air quality were assessed for Middle Eastern metropolitan areas. Significant reductions in the levels of NO2, SO2, and CO were noted. Nighttime SUHI intensity decreased during the lockdown, mainly in small cities. Long-term climate change matters when interpreting SUHI changes during lockdown.